Viscosity solution of linear regulator quadratic for degenerate diffusions - Baten, Md Azizul (North Atlantic Science Publishing Company, 2006)
The paper studied a linear regulator quadratic control problem for degenerate Hamilton-Jacobi-Bellman (HJB) equation.We showed the existence of viscosity properties and established a unique viscosity solution of the degenerate HJB equation associated with this problem by the technique of viscosity solutions.